(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses generally accepted phrases, their correspondences and differences from fashionable phraseological units using the example of somatic phraseological units of the village of Khusher, Sukhsky district of the Republic of Uzbekistan. Meaningful expressions of stable somatic expressions and cases of their